PENANGANAN ANSIETAS PADA PENYAKIT KRONIK DI RUMAH APUNG - Suntoro Suntoro; Shinta Yuliana Hasibuan; Maria Ayu Florensa; Ira Dewi; Evanny Indah; Heman Heman; Windy Zega; Janwar Olang; Veronica Paula (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2025)
Muara Angke, as a fishing port in Jakarta, experiences high levels of nighttime activity, which risks affecting the health of the local community. Chronic diseases such as diabetes, hypertension, and heart disease are on the rise, causing anxiety in patients. Anxiety in chronic diseases is triggered by the psychological and physical effects of these conditions. Research shows that anxiety is twice as high in patients with chronic diseases compared to the general population. A holistic approach to treating anxiety and chronic diseases is very important. This Community Service (PkM) activity aims to increase understanding and treatment of chronic diseases and anxiety in Muara Angke. The methods include health checks and counseling on chronic diseases and anxiety, with stages of preparation, implementation, and evaluation. A total of 56 participants took part. The results showed an increase in knowledge about chronic diseases and anxiety management based on pre- and post-tests. The evaluation also showed the community's enthusiasm and hope for similar activities in the future. In conclusion, a holistic approach that integrates physical and mental care has proven to be effective in improving the quality of life of the community in Muara Angke, while emphasizing the importance of regular health checks and proper anxiety management.